"I've spent a lot of the last two years just waiting for the world to not be terrible" : first-year undergraduate students' experience in a pandemic : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Psychology at Massey University, Albany, New Zealand - Liu, Siqi (Massey University, 2022)
In New Zealand, the COVID-19 pandemic arrived soon after the 2020 academic year began, posing additional challenges for first-year students navigating the transition to university while adapting to the pandemic. This thesis explores the experience of first-year students as they navigate this dual challenge. Using Interpretative Phenomenological Analysis (IPA), three participants from Massey University Albany Campus were interviewed to describe the pandemic’s impact on their wellbeing using the Te Whare Tapa Whā model, and its impact on their university experience and day-to-day learning. Analysis revealed four themes. In Disruption, the participants struggled with the very concept of a pandemic, causing intangible losses and grief. Wellbeing focussed on the pandemic’s impact on participants’ physical and mental health. The participants demonstrated divergent pathways to mental ill-health over time. Lockdown with Others highlighted how lockdown brought the household members’ different lifestyle needs into conflict and created distractions to the participants’ studies. Lastly, Studying during the Pandemic covers the participants’ initial adjustment to the university and their experience during Auckland’s two lockdowns. The participants reported less collaboration with others and reduced motivation when studying online. This thesis is the first to examine the collision of the pandemic and first-year university experience in New Zealand. The results highlight the pandemic’s lasting impact on the participants’ worldview. As with other research, the participants had unrealistic expectations of university. They attributed the failure to experience their idealised university life to the pandemic, perceiving their university experience as not a genuine one. Particular findings of note include the unintended impact of the university’s grade-adjustment policy reducing student motivation for learning; the impact of sleeping patterns during the lockdown on household dynamics; and the participants’ framing of physical exercise during the lockdown as a space-claiming action. Practice recommendations based on these findings include clear communication of academic expectations at university to first-year students; incorporating independent learning into the core first-year curriculum; and avoiding technology solutionism in online learning by positioning authentic relationships between faculty and students, and between the students, as the basis of the student experience.
Keywords: 520304 Health psychology